Absent pulmonary valve syndrome. Surgical correction with pulmonary arterioplasty. - Rao, P S (1983)
A 13 month old child with classic features of absent pulmonary valve with tetralogy of Fallot underwent successful surgical repair by closure of the ventricular septal defect, relief of the right ventricular outflow tract obstruction, and partial resection and plastic repair of the aneurysmally dilated pulmonary arteries. Cardiac catheterisation data and clinical follow up for more than 18 months after the operation indicated excellent results. It is suggested that plastic repair of the aneurysmally dilated pulmonary arteries along with closure of the ventricular septal defect and relief of the right ventricular outflow tract obstruction should be performed early, perhaps between 1 and 2 years of age.